Small bowel obstruction caused by intramural hematoma secondary to warfarin therapy: A report of two cases - Naime ALTINKAYA; Alper PARLAKGÜMÜŞ; Şenay DEMİR and Özlem ALKAN and Tülin YILDIRIM (Turkish Journal of Gastroenterology, 2019)
-